Effect of stem-bark extract of some common plants on non-target fresh water fish Channa marulius (Ham.) - Singh, D; Singh, A (Indian Journal of Fisheries, 2011)
Stem-bark extracts of four different plants (Euphorbia royleana, Jatrophagossypifolia, Nerium indicum and Thevetia peruviana) caused mortality andbiochemical changes in freshwater non-target fish Channa marulius. It wasfound that dilute stem-bark powder was effective in killing the fishes. The rankingof toxicity of four plants was N. indicum > E. royleana > J. gossypifolia andT. perucviana. Biochemical changes were observed in gonad tissue, after exposureto 40% and 80% of LC50 (24h) of stem-bark extract of all plants. Withdrawalexperiments, showed recovery in total protein, total free amino acid,while partial slow recovery observed in glycogen level after 144 h on terminationof experiment. It has been suggested that the alterations at both level (metabolicand enzyme) is due to activation of protein kinase C. These extracts showmortality at higher concentration and recovery after 7th day of withdrawal. So,the lower doses of purified form of stem-bark can be used as bio-pesticides forthe control of aquatic weeds without environmental hazards.